Association between LDL/HDL ratio and hypertension in Chinese middle-aged and older adults: a cross-sectional and longitudinal analysis based on CHARLS LDL/HDL ration and hypertension - Lai, Weicheng; Chen, Xiao; Wang, Lerui; Wu, Liangxiu; Li, Xin; Zhou, Boda (Frontiers in Endocrinology, 2025)
IntroductionHypertension is a global public health issue and major risk factor for cardiovascular disease (CVD). Low-density lipoprotein/high-density lipoprotein ratio (LDL/HDL Ratio, LHR) is an important indicator of lipid metabolism related to CVD. However, the relationship between LHR and the prevalence and incidence of hypertension has not been reported in large populations. This study aims to investigate the association between LHR and hypertension in middle-aged and elderly population.MethodsThis study utilized the China Health and Retirement Longitudinal Study (CHARLS) database from 2011 to 2020. Cross-sectional study was employed to analyze the association between LHR and the prevalence of hypertension; longitudinal analysis was used to examine the association between LHR and the incidence of hypertension. Eligible participants were adults aged 45 years and older with complete LHR and self-reported hypertension records. Multivariate logistic regression, smooth curve fitting, threshold effect analysis was performed.ResultsIn the cross-sectional study, we included 13,150 participants. After adjusting for potential confounders, each one-unit increase in LHR was associated with a 22% increase in the prevalence of hypertension (OR = 1.22, 95% CI: 1.15-1.30, P < 0.0001). The association between LHR and hypertension was consistent across different subgroups, with higher LHR being more strongly associated with increased hypertension prevalence in females and non-smokers. Our results revealed a linear relationship between LHR and hypertension prevalence. Longitudinal analysis showed that, among participants without hypertension in 2011, after 7 years of follow-up, the association between LHR and hypertension incidence remained robust after adjusting for a wide range of demographic, clinical, and biochemical variables (P < 0.05).ConclusionsThese results demonstrated significant positive association between LHR and the prevalence & incidence of hypertension, in a nationwide representative middle-aged and elderly population in China.